Estimated impact of novel coronavirus‐19 and transplant center inactivity on end‐stage renal disease‐related patient mortality in the United States. Issue 8 (31st May 2021) - Peters, Thomas G.; Bragg‐Gresham, Jennifer L.; Klopstock, Annie C.; Roberts, John P.; Chertow, Glenn; McCormick, Frank; Held, Philip J.
Abstract: To predict whether the COVID‐19 pandemic and transplant center responses could have resulted in preventable deaths, we analyzed registry information of the US end‐stage renal disease (ESRD) patient population awaiting kidney transplantation. Data were from the Organ Procurement and Transplantation Network (OPTN), the US Centers for Disease Control and Prevention, and the United States Renal Data System. Based on 2019 OPTN reports, annualized reduction in kidney transplantation of 25%–100% could result in excess deaths of wait‐listed (deceased donor) transplant candidates from 84 to 337 and living donor candidate excess deaths from 35 to 141 (total 119–478 potentially preventable deaths of transplant candidates). Changes in transplant activity due to COVID‐19 varied with some centers shutting down while others simply heeded known or suspected pandemic risks. Understanding potential excess mortality for ESRD transplant candidates when circumstances compel curtailment of transplant activity may inform policy and procedural aspects of organ transplant systems allowing ways to best inform patients and families as to potential risks in shuttering organ transplant activity. Considering that more than 700 000 Americans have ESRD with 100 000 awaiting a kidney transplant, our highest annual estimate of 478 excess total deaths from postponing kidney transplantation seems modest.